Eksplorasi Simbol Konvensional dan Universal dalam Penciptaan Video Art Kampanye Anti Perang dan Kekerasan “WARKAHOLIC” dengan Teknik Animasi 3D - Arif Sulistiyono (Rekam: Jurnal Fotografi, Televisi, Animasi)
At The End of 2010 to 2011 there has been a political crisis in MiddleEastern countries and parts of North Africa. The movement called "JasmineRevolution" caused by poor socioeconomic situation in the region, while itspresidents has been living rich in power for decades. It was raised the anger of the people and cause lot of protest to raising down the Presidents. Most of the presidents refused to resign and against the protester violently. The thousands of people have been killed and injured due to the demonstrations and civil war during the conflict. The Indonesian people must be wary to prevent leadership crisis's revolution. They need to be aware that the war and violence conflict caused suffering continously and harmfull for both of them."Warkaholic" is a manifestation of the artist's social responsibility to deliver the message through their artworks. It formed into the video arts and the topic of its art works are stop war and violence campaign. This video arts does not emphasize the personal subjectivity aspects as a fine art works. It will be more objective and easily understood for the public in general and can be seen by peoples through any audiovisual media.The methods of art works's realization are narrative style approach andapplying universal symbol, iconic, connotative to the visual and sound elements of the object. Visual storytelling content can be understood by peoples as a representation of the impact of war and violence. The Supers or text is to be the key of the public's message to stop war and violence. The computer 3D animation technique is used to create realistic  visualization and to make something impossible in live action technique can be relatively possible.